Stiff Matter in the Universe - Øyvind G. Grøn (Physical Science: New Insights and Developments Vol. 1, 2025)
The main objective of this article is to introduce a novel mathematical expression for the comoving volume element in a flat universe that includes a cosmological constant, cold matter, and stiff matter and utilised this to derive constraints on the amount of stiff matter in the universe based on the Planck measurements of the Hubble parameter. These constraints are then examined to assess whether stiff matter could potentially resolve the Hubble tension. The findings show that the difference between the Hubble constant in a universe with stiff matter and the \(\)CDM- universe is positive. Hence, the Hubble constant is larger with stiff matter than without. This goes in the right direction since the point of departure for this calculation is the value of the Hubble constant as determined by the Planck measurements, and this value is lower than the late universe measurements. The findings also indicate that the Planck measurements impose an upper limit on the current value of the density parameter of stiff matter, \(Ω\)S0 < 5 . 10-23 , which is insufficient to resolve the Hubble tension.